# Solve for x. 3(3x - 1) + 2(3 - x) = 0

**Solution:**

Given equation: 3(3x - 1) + 2(3 - x) = 0

We need to solve for x.

Using distributive property, we do multiplication over subtraction and then group the like terms.

⇒ 9x - 3 + 6 - 2x = 0

⇒ 7x + 3 = 0

⇒ 7x = -3

⇒ x = -3/7

The solution for 3(3x - 1) + 2(3 - x) = 0 is -3/7

## Solve for x. 3(3x - 1) + 2(3 - x) = 0

**Summary:**

The value of x for the given expression 3(3x - 1) + 2(3 - x) = 0 is x = -3/7.

Math worksheets and

visual curriculum

visual curriculum